شرعية الإجراءات الجزائية السابقة على المحاكمة وتطبيقاتها في القانون والقضاء الإمارا تي - يعقوب مصطفى محمود صالح; Yacoup Mustafa Mahmoud Saleh (Universiti Sains Islam Malaysia, 2024)
Matric :4192727(FSU)